Analysis of Risk Management and Entrepreneurship Orientation Towards the Sustainability of MSME Businesses - Vini Arsih; Animah (PT FORMOSA CENDEKIA GLOBAL, 2024)
The aim of this research is to analyze the influence of risk management and entrepreneurial orientation on the sustainability of MSME businesses. This research uses quantitative methods with the research population being the Gold Mutiara MSMEs in Mataram City, totaling 60 MSMEs, of which 56 MSMEs were sampled. Data analysis in this study used SPSS 25. The results of this study show that the variables of risk management and entrepreneurial orientation have a positive effect on the sustainability of the Emas Mutiara MSME business in Mataram City. Based on these findings, it is recommended that Emas Mutiara MSMEs practice risk management and entrepreneurial orientation to improve the sustainability of MSME businesses.